Teledentistry – A Multicentric Approach to Promote Oral Health Among Individuals with Cleft Lip and Palate in Rural Areas - Banu Priya S; Ganesh, Akila; Muthu MS; K, Vignesh; Subramanian C, Siva; Subramaniyan B; Gayathri SR (National Journal of Community Medicine, 2025)
Teledentistry is a novel mode of promoting oral health care. It provides an opportunity for families living in remote areas to access timely/periodic oral healthcare. This approach aims to promote oral health in individuals with repaired cleft lip and palate (CLP) through teledentistry and evaluate its reach. A teledentistry model was implemented in a cohort of individuals with CLP from three rural areas. Teledentistry involved teleconsultations, telemonitoring, and teleeducation through real-time and mobile health methods from a tertiary care center. Over five months, 138 individuals with CLP were teleconsulted, with 64 (46.3%) requiring dental treatment. Teledentistry successfully reached 138 individuals from rural areas, promoting oral health. This approach demonstrates the potential of teledentistry in increasing access to oral healthcare services for individuals with CLP in rural areas.